Chlorine residual behavior in water disinfection using combined sand media with chlorine application - Asyfiradayati, Rezania; Wulandari, Windi; Berlian N, Jenita; Mohd Yatim , Siti Rohana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. Water is a need for every human being in all parts of the world. The demand for water, particularly clean water, is expected to increase in line with population growth. In Indonesia, wells providing access to both shallow and deep groundwater sources serve as the primary source of clean water Microbiological contamination of water causes a bad impact, especially on health. The water supply system is a fundamental component of sustainable urban development. Nevertheless, it frequently encounters a range of complex challenges, especially in developing nations. The purpose of article. The objective of this study is to investigate the concentration of residual chlorine over varying contact times using different media combinations, namely black sand, silica sand, and white sand, to evaluate their effectiveness in sustaining chlorine levels during water treatment. Research methods. This research employed a quasi-experimental design to evaluate residual chlorine levels in treated water using various types of sand integrated with chlorine within diffuser pipes. A total of 720 liters of water was used, divided into 36 reservoirs. holding 2.5 mg of chlorine each of which contained 20 litres and 500 grams of one of three types of sand: black sand, white sand, or silica sand. Water samples in 20-litre containers were treated with a chlorine sprayer for exposure periods of 30, 45, and 60 minutes. The study assessed several parameters, including temperature, pH, total dissolved solids (TDS), and residual chlorine. Data were analyzed and presented using univariate and bivariate tables, with statistical testing conducted using one-way ANOVA. Result. The results indicated that the chlorine diffuser containing white sand exceeded the permissible residual chlorine threshold at contact times of 45 and 60 minutes. Statistical analysis using one-way ANOVA revealed a significant difference in residual chlorine concentrations between the silica sand and black sand media (p < 0.05). However, no statistically significant difference was observed in the chlorine concentrations over time for the white sand diffuser. These findings suggest that white sand may lead to prolonged chlorine retention, potentially resulting in concentrations above recommended limits Scientific novelty and practical value. for the first time, an analysis that the various types of sand in the chlorine diffuser have differences in the remaining chlorine in the water so that it can be used as a reference for further research in water treatment.